Good Corporate Governance dan Kinerja Non Keuangan - Retno Wulandari; Tumirin Tumirin; Suwandi Suwandi (JIATAX (Journal of Islamic Accounting and Tax), 2018)
The purpose of the research is to know the relationship between corporate governance and non financial corporate performance. The rating of corporate governance perception index (CGPI) is used by the Indonesian Intitute for Corporate Governance to meansure the corporate governance implementation, employee productivity as a business internal prespective measurement, and employee development corverage as a learning and growth perspective measurement. This research also uses control variable that are activa composition and growth opportunities. Using a multiple regression to test the hypothesis that corporate governance and non financial corporate performance are positively related. The analysis shows that there is a significant positive relationship between corporate governance index and employee productivity, but there is no significant positive between corporate governance and employee development coverage.